The Effect of Digital Marketing and Product Diversity on Interests and Impact on Student Decisions in Choosing Private Universities in Padangsidimpun City - Masnilam Hasibuan (Universitas Dharma Wacana, 2022)
The research aims to analyze the role of digital marketing and product diversity on purchasing decisions through consumer interest as an intervening variable. Digitalization in the era of the industrial revolution 4.0 is vital for every business unit as input to be considered in consumer decision-making. Product diversity is a measure that is no less important than digital marketing because its role is very helpful as a medium in determining purchasing decisions. This research uses quantitative research methods with descriptive and verification analysis. The research unit is a private tertiary institution in the city of Padangsidimpun, namely Padangsidimpuan Graha Nusantara University, Padangsidimpuan Aufa Royhan University, South Tapanuli Muhammadiah University, and South Tapanuli Educational Institute with research subjects being active students and the sampling technique was carried out by proportional random sampling. Sources of data in this study are primary data and secondary data. The analysis technique in this study uses the structural analysis technique of the equation model. The study results show that digital marketing and product diversity influence purchasing decisions directly and through consumer interest. The findings of this study indicate that product variety has the greatest influence on customer interest, which indicates that students, before making their choice, first pay attention to product diversity consisting of a choice of the study program, choice of study program accreditation, absorption of the study program for work and program offers scholarship studies.